2005
DOI: 10.3354/meps289263
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal effects determine size, growth and performance in larvae of a tropical reef fish

Abstract: Larval mortality in marine fishes is strongly linked to individual life history traits such as size and growth, but the processes that influence variability in these traits are poorly understood. We explore the relative importance of maternal and paternal influences and water temperature on the larval growth and performance characteristics of the tropical clownfish Amphiprion melanopus (Pomacentridae). Larvae were reared from an incomplete 4 male × 4 female diallel breeding cross at 2 temperatures (25 and 28°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 49 publications
(61 reference statements)
3
85
1
Order By: Relevance
“…Larger and older marbled sole females produced larger eggs. Similar relationships between maternal attributes and egg size, larval size, or larval quality have been reported for many fishes (e.g., Buckley et al, 1991a, b;Chambers and Leggett, 1992;Chambers and Waiwood, 1996;Kjesbu et al, 1996;Solemdal, 1997;Marteinsdottir and Steinarsson, 1998;Keckeis et al, 2000;Riveiro et al, 2000;Johnston and Leggett, 2002;Fox et al, 2003;Berkeley et al, 2004;Trippel and Neil, 2004;Green and McCormick, 2005). Although we found that larger larvae had higher feeding ability, direct correlations between feeding rate and maternal attributes were not significant.…”
Section: Discussionsupporting
confidence: 84%
“…Larger and older marbled sole females produced larger eggs. Similar relationships between maternal attributes and egg size, larval size, or larval quality have been reported for many fishes (e.g., Buckley et al, 1991a, b;Chambers and Leggett, 1992;Chambers and Waiwood, 1996;Kjesbu et al, 1996;Solemdal, 1997;Marteinsdottir and Steinarsson, 1998;Keckeis et al, 2000;Riveiro et al, 2000;Johnston and Leggett, 2002;Fox et al, 2003;Berkeley et al, 2004;Trippel and Neil, 2004;Green and McCormick, 2005). Although we found that larger larvae had higher feeding ability, direct correlations between feeding rate and maternal attributes were not significant.…”
Section: Discussionsupporting
confidence: 84%
“…For a range of taxa across a variety of habitats, individuals that start juvenile life with a large size often perform better than smaller conspecifics. This pattern has been shown for gastropods (Spight 1976, Gosselin 1997, Moran & Emlet 2001, mussels (Phillips 2002), barnacles (Thiyagarajan et al 2003), ascidians (Marshall et al , 2006, beetles (Fox 2000, Clark et al 2011, isopods (Tsai & Dai 2001), spiders (Walker et al 2003), fish (Green & McCormick 2005, Fisher et al 2007, and birds (Krist 2011). Therefore, intraspecific variation in offspring size is of fundamental ecological and evolutionary importance (Marshall & Keough 2008).…”
Section: Introductionmentioning
confidence: 85%
“…Maternal qualities related to condition may be relevant to growth potential of larvae (Marteinsdottir and Steinarsson 1998, Green and McCormick 2005, Swain and Nayak 2009, Perez and Fuiman 2015. Under natural conditions, higher values of δ 15 N have shown greater growth potential in bullet tuna larvae (Auxis rochei) and in the Mediterranean anchovy (Engraulis encrasicolus) (Laiz-Carrión et al 2011, Quintanilla et al 2015.…”
Section: Isotopic Variationmentioning
confidence: 99%